Primary honey dressing of perineal wounds and acacia honey consumption to improve the quality of life of postpartum mothers - Sri Suparti; Retno Widowati; Rini Kundaryanti (Nursing and Health Sciences Journal (NHSJ), 2025)
Perineal wounds, postpartum pain, anemia, and low breast milk production are common problems in postpartum mothers that can reduce their quality of life. Topical and oral use of honey has been shown to accelerate wound healing, reduce pain, increase hemoglobin levels, and increase breast milk production. The study's objectives were to determine the effectiveness of primary honey dressing of perineal wounds and acacia honey consumption in improving the quality of life of postpartum mothers. This pre-experimental study used a quasi-experimental design with a pretest-posttest with a control group. Using a total sampling technique, the sample size was 40 postpartum mothers, consisting of 20 in the treatment group and 20 in the control group. The intervention consisted of a primary honey dressing on the perineal wound and acacia honey consumption for 21 days. The instruments used included the REEDA scale, the Numeric Rating Scale (NRS), hemoglobin level measurements, and breast milk volume measurements. Data analysis used the Independent T-Test and Paired T-Test. There were significant differences between the treatment and control groups in terms of perineal wound healing (p<0.05), reduced pain intensity (p<0.05), increased hemoglobin levels (p<0.05), and increased breast milk production (p<0.05). Primary honey dressing on the perineal wound and acacia honey consumption was effective in accelerating wound healing, reducing postpartum pain, increasing hemoglobin levels, and increasing breast milk production, all of which contributed to an overall improvement in the quality of life of postpartum mothers. It is recommended that healthcare professionals consider using honey in obstetric care, particularly in postpartum maternal monitoring. This implementation can be a promotive and preventive strategy in maternal health care.